Pesan Tersirat Dalam Lirik Lagu “The A Team” Karya Penyanyi Eheeran: - Nasution, Elza Hasyim; Nugraha, Gentha; Sazali, Hasan (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The study was intended to describe a music video titled "The A Team" that Ed sheeran sang. The study employed qualitative research methods because the writers considered the problem to be so complex and dynamic that the data that would be obtained from the selected sources would be chosen by a more scientific method - the direct interview with the source and thus have a scientific answer. The sources include students and communications science students who were in the seventh semester. Researchers will ask questions that are pertinent about the video clip and lyrics of the song "The A Team" sung by Ed sheeran. Keywords: Study,Qualitative, Communication